Democracy of People: Beyond the Citizen and the Individual - Lázaro Pulido, Manuel (Contributions to Political Science, 2023)
To speak of the democratic state as the space for citizen participation in political life, it is an intellectual convention. Democracy is a form of government where individuals have the right to present their ideas in public and organise themselves, often by joining political parties. The semantic diversity employed to define those actors of democracy (individual, citizen, even, party member…) designates concrete ways in which people express themselves in the social realm. However, they may render invisible the fundamental concept that defines the human being: the person. Taking as starting point that human being is essentially a person, I contend that the specific conceptual reduction of the person to the individual-citizen dialectic in political-social life is at the basis of one of the fundamental deficits of democratic states, for it may constrain political actors to a specific sphere of their existence. This could lead to political disaffection and pervert the fundamental ethical and legal mechanisms of democracy itself, like the protection of fundamental human rights, which belong to the person as such, beyond his or her individual or civic status.
Keywords: democracy; people; Scopus(2)